Understanding the effect of processing and species on milk proteins during digestion : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Biochemistry at Massey University, Manawatū, New Zealand - Maidment, Catherine Ann (Massey University, 2025)
Milk is an important source of protein in a balanced human diet. Milk proteins not only have high nutritive value but also have biological properties. Milk composition and structure vary based on factors such as species, processing methods, and lactation stage. These differences are believed to affect digestion by influencing the breakdown of milk proteins, fats, and carbohydrates, as well as the rate and efficiency at which nutrients are absorbed in the gastrointestinal tract. The overall objective of this PhD thesis was to investigate how milk proteins from different species (cow, sheep, goat, and deer) are affected by digestibility under varying processing treatments (heating and homogenisation). Digestibility was assessed by the amount and types of bioaccessible peptides generated during gastrointestinal digestion. A dynamic in vitro digestion model (human gastric simulator (HGS)) was used for this study. Size exclusion chromatography was employed to measure the amount of peptides generated throughout digestion, with significant differences determined by a p-value threshold of 0.05. Mass spectrometry was used to analyse the types of peptides, requiring peptides to be present in at least two-thirds of the samples for inclusion. To assess the validity of the results obtained using the HGS model, comparisons were made with the peptide profiles generated using an in vivo (pig) digestion model. In addition, further work was undertaken looking into the protein composition of deer milk throughout the different lactation stages. This study investigating digestibility found differences in the amount and types of bioaccessible peptides generated throughout gastric digestion in milk from different species. Overall, deer milk produced the most peptides, while goat and sheep milk produced the least. Ruminant species also affected which regions of the parent protein were resistant to digestion as well as their bioactive properties. In contrast, processing treatment did not have as significant an effect on the amount and types of bioaccessible peptides but did affect the digestion kinetics. Differences were only observed during early digestion and appeared to be species dependent. Similarities were found in the peptides released throughout gastric digestion between the HGS model and the in vivo pig model, which suggests that the HGS model is suitable for the study of gastric digestion of protein-rich food. However, the peptide profiles differed during the intestinal stage indicating that the intestinal step attached to the in vitro model needs improving to fully mimic the dynamic nature of in vivo digestion. The study investigating deer milk proteins found that proteins related to transport e.g. apolipoprotein E and vitamin D-binding protein and immunity e.g. osteopontin, immunoglobulin J and lactotransferrin were found to change throughout lactation. This is thought to reflect the changing needs of the newborn as well as the development and protection of the mammary gland over lactation. Proteins were investigated using mass spectrometry, and significant differences throughout lactation were determined using simple linear regression calculations and log fold change calculations, comparing protein levels between week 3 and week 16 of lactation. The results from this thesis will contribute to the knowledge of how milk composition and structure impact protein digestibility throughout gastrointestinal digestion. The information gained from this study may have important consequences for developing dairy products that deliver superior digestive and nutritional outcomes to targeted consumer groups.
Keywords: 300601 Beverage chemistry and beverage sensory science; 321002 Food properties (incl. characteristics and health benefits)